Evaluasi Sistem Informasi Akademik Satya Wacana Menerapkan Model for Mandatory Use of Software Technologies - Calvin Yakhin Pongmakamba; Johan J C Tambotoh (JURIKOM (Jurnal Riset Komputer), 2023)
There are many theories and methods that can be used to evaluate information systems. For example TAM, Wixom and Todd, DeLone and McLean, etc. These models are not suitable to evaluate information systems that are implemented in mandatory environments where the users have to use the system whether they prefer to use it or not. This study aims to explore the variables that can affect the level of use of SIASAT (Satya Wacana Academic Information System). This research was carried out to find out how significant the influence of the factors that can influence SIASAT users. This study using BSR (Behavioral Science Research) approach with quantitative methods through data collection using questionnaire. For data analysis, statistical analysis was carried out using PLS-SEM through SmartPLS 4 software. Based on the results of the study it can be interpreted that there is a significant relationship between performance expectations and user attitudes in SIASAT usage. This can be seen from the relationship between the variables PE -> AT which has the highest T-Statistic value, 24,877. Variabel with highest effect is the Information Satisfaction variable with an R-Square value of 0.655. Of the eight hypotheses tested, it was concluded that six of them were accepted and two were rejected. This is because the two hypotheses using the Use variable with a Cronbach's Alpha value below 0.7 (0.576) these variables considered unreliable thus two hypotheses are rejected.